2017
DOI: 10.1093/femsec/fix172
|View full text |Cite
|
Sign up to set email alerts
|

Variable plasmid fitness effects and mobile genetic element dynamics across Pseudomonas species

Abstract: Mobile genetic elements (MGE) such as plasmids and transposons mobilise genes within and between species, playing a crucial role in bacterial evolution via horizontal gene transfer (HGT). Currently, we lack data on variation in MGE dynamics across bacterial host species. We tracked the dynamics of a large conjugative plasmid, pQBR103, and its Tn5042 mercury resistance transposon, in five diverse Pseudomonas species in environments with and without mercury selection. Plasmid fitness effects and stability varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 44 publications
4
72
0
Order By: Relevance
“…The consequent fitness costs can limit plasmid survival because plasmid-bearers will be outcompeted by plasmid-free cells that do not suffer the cost [2]. Beneficial genes carried by the plasmid cannot ensure its long-term persistence, as these genes can recombine onto the chromosome [3, 4]. An important mechanism allowing plasmid survival is compensatory evolution whereby mutations in chromosomal and/or plasmid genes ameliorate fitness costs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The consequent fitness costs can limit plasmid survival because plasmid-bearers will be outcompeted by plasmid-free cells that do not suffer the cost [2]. Beneficial genes carried by the plasmid cannot ensure its long-term persistence, as these genes can recombine onto the chromosome [3, 4]. An important mechanism allowing plasmid survival is compensatory evolution whereby mutations in chromosomal and/or plasmid genes ameliorate fitness costs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of S α+δ values across phylotypes and conditions confirmed that the plasmid effect is a phylotype and context dependent feature. In fact, population-level studies have repeatedly revealed that plasmid effects are indeed determined by strain-specific factors [42,43]. We identify here, for the first time, individual specific plasmid effect within a complex microbial community.…”
Section: Discussionmentioning
confidence: 60%
“…The change in error bars is indicative of ongoing adaptation to the mixed culture conditions but, interestingly, I found no significant change in the number of pGW155B borne by R-cells during the competition ( Figure 2B, Mann-Whitney U-test p = 0.1 and ranksum= 15 for 3 replicates). Now, the cost of plasmid carriage is commonly measured using fitness [11,13,14,31,33] and this metric relies on growth rate [26,27]. How well does fitness predict the outcome of this competition?…”
Section: Resultsmentioning
confidence: 99%
“…So, here I asked what cost do microbes pay in each phase of microbial growth. The Malthusian parameter, metric widely used to estimate microbial and tumour growth rates [11,14,[26][27][28][29][30][31][32][33], could-in principle-reflect differences in lag, cell density during the stationary phase or, indeed, in growth rate [26]. But it cannot inform which trait is sensitive, and what cost they pay.…”
Section: Introductionmentioning
confidence: 99%